Automatic lock entrance gate controller/ Hariol Idail Mohd Yusof and Norhafidi Jafar - Mohd Yusof, Hariol Idail; Jafar, Norhafidi (2000)
Final project is a part of a course structure as a fulfill for students in their final year. The project is compulsory to us as a final year student for course Diploma In Electrical Engineering. The purpose of this project is to produces a student a main power with a very high skill and able to handle a responsibility given like a project. They should prepared to deliver a creativity ideas and good interpersonal image to their future employer. It can make students used all of their knowledge, creative and skills to purpose, create and trouble shoots the project. It is because all of the theories and skills, they have learned from the project 1 and project 2 are used. As the time change, the way of life is also change with them. Nowadays, the rapid changes in quality of life require new technologies so as to fixed with them. It is necessary to design new system that can make everything as simpler as possible to operate. The main purpose of this project is actually based on the needs of some peoples nowadays to overcome obstacle in their everyday life. This project offers use an automatically to open the gate with using a motor to operate it. The motor is connected to the receiver circuit. When a receiver circuit received a signal from transmitter, the motor will move to the right or the left with following the signal it receive. It will cause, the gate can opened or closed.